Constitutional Court statistics for the 2016 term. Issue 1 (2nd January 2018) - Makuwa, Amogelang; Mhiribidi, Rudo; Chagopa, Adelaide; Kathi, Thandeka; Chamberlain, Lisa
Abstract: This note provides descriptive statistics on the work of the Constitutional Court of South Africa (the Court) in 2016, organised in a number of tables. The method of constructing each table is given in the text that follows it. The objectives and methods of this annual set of statistics are more fully laid out in the 1995 edition and subsequent editions of the SAJHR. Part I covers those decisions in which the Court produced a written judgment while Part II covers applications that were considered in chambers and dismissed without a judgment being given.